A ubiquitous amino acid source for prokaryotic and eukaryotic cell-free transcription-translation systems - Nagappa, Lakshmeesha K.; Sato, Wakana; Alam, Farzana; Chengan, Kameshwari; Smales, Christopher M.; Von Der Haar, Tobias; Polizzi, Karen M.; Adamala, Katarzyna P.; Moore, Simon J. (Frontiers in Bioengineering and Biotechnology, 2022)
Cell-free gene expression (CFE) systems are an attractive tool for engineering within synthetic biology and for industrial production of high-value recombinant proteins. CFE reactions require a cell extract, energy system, amino acids, and DNA, to catalyse mRNA transcription and protein synthesis. To provide an amino acid source, CFE systems typically use a commercial standard, which is often proprietary. Herein we show that a range of common microbiology rich media (i.e., tryptone, peptone, yeast extract and casamino acids) unexpectedly provide an effective and low-cost amino acid source. We show that this approach is generalisable, by comparing batch variability and protein production in the following range of CFE systems: Escherichia coli (RosettaTM 2, BL21), Streptomyces venezuelae and Pichia pastoris. In all CFE systems, we show equivalent or increased protein synthesis capacity upon replacement of the commercial amino acid source. In conclusion, we suggest rich microbiology media provides a new amino acid source for CFE systems with potential broad use in synthetic biology and industrial biotechnology applications.